Comprehensive Benefit/Cost Analysis of Utilizing PEV Parking Lots as Virtual Energy Storage for the Energy Supply Sustainability of Future Distribution Systems - Zeng, Bo; Sun, Bo; Mu, Hongwei; Wang, Yuqing; Wei, Xuan; Wang, Libin (Frontiers in Energy Research, 2021)
The proliferation of plug-in electric vehicles has led to increased public charging infrastructure in cities worldwide. Grid-connected parking lot spaces are the most common charging option due to their technological readiness and convenience of adoption. Since the batteries aggregated by parking lots can be regarded as virtual energy storage, grid-connected parking lots are expected to provide many benefits to the urban distribution grid. This paper proposes a comprehensive methodological framework to evaluate the potential benefits and costs of utilizing grid-connected parking lot spaces to promote energy supply sustainability in future power distribution grids. Capacity-value-based and cost effectiveness indexes are developed, which quantify the potential contribution of parking lots to power supply reliability and the associated economic implications. To realistically describe the available generation capacity of parking lot resources, a comprehensive model is presented, which explicitly considers the impact of external stimuli (incentive grades) on the behavioural patterns of lot users. Vehicle user responsiveness to incentive grades is derived from social field surveys. To conduct the evaluation, a hybrid Monte Carlo simulation algorithm is employed. The proposed methodology is illustrated on a real distribution grid in Beijing. The results confirm the effectiveness of our proposed approach and support practical policy suggestions.